Consciousness of dairy farmers about leptospirosis disease as a zoonosis - Jadav, SJ; Patel, JK (Indian Journal of Dairy Science, 2021)
The study was carried out to assess the consciousness of dairy farmers about leptospirosis disease as a zoonosis. Using the simple random sampling method, 180 dairy farmers from 36 villages of 6 talukas of Panchmahals and Mahisagar districts of Gujarat state (India) were selected. The majority of dairy farmers (88.34 per cent) had medium to high level of consciousness about leptospirosis disease. The majority of the dairy farmers had very low to low level of knowledge (83.89 per cent), very high level of sensitivity (62.78 per cent) and favorable to most favorable attitude (95.55 per cent) towards the control of leptospirosis disease as a zoonosis. The relationship between education, extension participation, mass media exposure, internet exposure, professional training received, scientific orientation, innovation proneness and economic motivation of dairy farmers with their consciousness on leptospirosis disease were found to be a positive and significant. Dairy farmers can enhance their consciousness about leptospirosis disease through participation in different extension activities with using mass media, internet and other psychological variables.